"A healthy outside starts from the inside": A matter of sustainable consumption behavior in Italy and Pakistan. (5th April 2021) - Ishaq, Muhammad Ishtiaq; Sarwar, Huma; Ahmed, Roheel
Abstract: The aim of this research is to determine people's motives when purchasing organic food and how these motives are moderated by price sensitivity and ethical concerns in a cross‐cultural setting. A highly structured questionnaire was used to collect the data from 673 Italian and 594 Pakistani consumers, using the convenience sampling technique. Based on the etic research approach, the measurement invariance tests were performed, and data were analyzed using structural equation modeling. The results indicate that environmental concerns and health‐consciousness are significant predictors of subjective norms and purchase attitudes among Italian consumers. Food safety concern proved the strongest predictor of purchase attitude and perceived behavioral control among Pakistani consumers. The results also confirm the moderating role of ethical concerns and price sensitivity in buying organic food in both cultures. In terms of originality, this study fills significant gaps in the literature, particularly regarding the roles of attitude, behavioral control, and subjective norms in consumer buying motives and purchasing intentions in cross‐cultural studies but more importantly, the results validate that consumer concerns across the globe are related to the Sustainability Development Goals and the U.N. 2030 agenda, which aptly provides a blue print for the development and developmental goals and concerns across nations.